2004
DOI: 10.1177/1028315303260832
|View full text |Cite
|
Sign up to set email alerts
|

Internationalization Remodeled: Definition, Approaches, and Rationales

Abstract: The world of higher education is changing and the world in which higher education plays a significant role is changing. The international dimension of higher education is becoming increasingly important, complex, and confusing. It is therefore timely to reexamine and update the conceptual frameworks underpinning the notion of inter-nationalization in light of today’s changes and challenges. The purpose of this article is to study internationalization at both the institutional and national/sector level. Both le… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
1,259
2
349

Year Published

2012
2012
2019
2019

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 1,738 publications
(1,763 citation statements)
references
References 4 publications
11
1,259
2
349
Order By: Relevance
“…The topic of internationalization of American higher education has received tremendous amount of attention from researchers and scholars in the past decades (Altbach, 2004;Knight, 2004;Scott, 2000;Van Der Wende, 2001). In the late 1990s, the American Council on Education (ACE) published a series of reports on internationalization in American universities and supportive programs to bring about internationalization (ACE 1999(ACE , 2003.…”
Section: History Of International Education In American Universitiesmentioning
confidence: 99%
See 2 more Smart Citations
“…The topic of internationalization of American higher education has received tremendous amount of attention from researchers and scholars in the past decades (Altbach, 2004;Knight, 2004;Scott, 2000;Van Der Wende, 2001). In the late 1990s, the American Council on Education (ACE) published a series of reports on internationalization in American universities and supportive programs to bring about internationalization (ACE 1999(ACE , 2003.…”
Section: History Of International Education In American Universitiesmentioning
confidence: 99%
“…According to Knight (2004), internationalization includes "academic standards, cultural diversity, student and staff development, and income generators" (p. 20). Knight and de Wit (1995) and Hsu (2012) envisioned internationalization with the implementation of a wide range of policies, services, and activities designed to integrate intercultural and international dimensions into an institution's student services, curricula teaching, and research.…”
Section: The Ethos Approachmentioning
confidence: 99%
See 1 more Smart Citation
“…The main components of internationalisation of higher education are global competition for talents, recruitment of international students, development of international branch campuses, exchange programs for students, staff and scholars, internationalisation of the curriculum, and research and education partnerships between institutions regionally and internationally (Khorsandi Taskoh, 2014;Knight, 2004;Sanderson, 2008). Beck (2012) asserts that internationalisation is a product of and response to globalisation.…”
Section: Introductionmentioning
confidence: 99%
“…According to Knight (2004), In the previous literature, it has been identified that a number of aspects influence entry mode selection. Among them, Dunning (1977Dunning ( , 1999 proposed that entry mode selection is influenced by three types of determinants: ownership advantages of a firm, location advantages of a market and internalization advantages of integrating transactions within the firm.…”
Section: Theory Of Multinational Enterprisementioning
confidence: 99%